Dramatización de ritos y ceremonias en las obras del Nuevo Teatro español: una corriente de oposición antifranquista en el teatro de las últimas décadas de la dictadura - Mańkowska, Joanna (Romanica Silesiana)
The practice of invoking rituals is one of the resources most often employed in the Spanish New Theatre: a play may represent a rite, or resemble a certain ceremony. The characters celebrate little daily ceremonies or acts, often blasphemous, involving a ritual victim. In this respect, Bilbatúa notes that one can even observe a certain trend in the theatrical practice, namely, resorting to ceremonies on a regular basis. This however, may only be justified when used in order to “highlight religious, sexual, political and other repressions in a way they appear in our sub‑consious”. The authors, who seem to share the opinion of Riaza that “ceremonial theatre is better suited to challenge bourgeois spectator”, engage in rituals to denounce highly ritualised socio‑political reality of the Francoist period, to deal with present problems alluding to human condition more generally, or to counter taboos and social conventions overwhelming human beings, and leading to frustration and permanent malaise they suffer from. Key words: the Spanish New Theatre, the theatre in the Francoist period, the theatre as an anti‑Francoist opposition, the ceremonial theatre, dramatization of rites and ceremonies